“Vow crosses” in Gorj county (Romania): symbolism and interpretation - Rogojanu, Dumitru-Cătălin; Boda, Gherghina (The Journal of Ethnology and Culturology, 2026)
“Vow crosses”, considered according to tradition as the resting place of the souls of the deceased or the “house of the soul”, are a unique custom in Romania, specific to some localities in Gorj County, such as Hurezani, Licurici, Aninoasa, Vladimir, Jupânești, Stejari and others. They are presented as crosses painted in various colors, representing religious figures, in rare cases with short verses, hanging in trees, at fountains, in the courtyard of churches, at gates, but most of them on the side of roads, their placement being made 40 days after death. Both the commemorative and vow crosses are made for the forgiveness of those who have departed from the living, an ancestral tradition whose origins are unknown, but which is respected with holiness after death. The symbolism of the forgiveness of the departed to heaven is abundantly represented by the vow corss which, on the one hand, sacralizes the space by its presence, on the other hand, constitutes a means of forgiveness, of relief of the soul of the deceased, because salvation is obtained through the cross. It can also be seen as a binder between the desire of the deceased to have such a cross made for him and between the duty to fulfill the promise by those who remain alive. Keeping a vow means fulfilling a promise made not only to the deceased, but also to God, the only one who can forgive sins.